REVIEW: Bill Gladstone's "Only Yesterday: Collected Pieces on the Jews of Toronto by Benjamin Kayfetz and Stephen A. Speisman" - Scheinberg, Ellen (Canadian Jewish Studies / Études juives canadiennes, 2015)
.